РЕЛЬЕФНИНГ РАҚАМЛИ МОДЕЛЛАРИНИ УЧУВЧИСИЗ УЧИШ АППАРАТЛАРИ ЁРДАМИДА ЯРАТИШ - Алиқулов, Ғолиб; Аралов, Музаффар (Innovatsion texnologiyalar, 2022)
Currently, in the conditions of the formation and development of the digital economy in the world, digital information is considered the main factor of production in all spheres of socio-economic activity. Demands for digital geospatial data are increasing, they are required to provide rational location related to various databases in order to build unified geographic information spaces within the framework of spatial development strategy. In the last decade, with the development of microelectronics, robotics, artificial intelligence, air technologies, the production of small-sized and uncomplicated unmanned aerial vehicles, which are successfully used in aerial photography, is actively developing.